1999
DOI: 10.1519/1533-4287(1999)013<0090:arotac>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Acute Cardiovascular Responses to Resistance Exercise of Healthy Young and Older Adults

Abstract: The purpose of this review was to summarize the acute cardiovascular responses of healthy young and older adults to resistance exercise and to review studies that have compared healthy younger and older populations. Intensity, duration, and active muscle mass are known to play important roles in the degree of pressor response elicited during resistance exercise in both young and older participants. Systolic, diastolic, and mean arterial pressure as well as heart rate rise in response to resistance exercise. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 47 publications
2
21
0
4
Order By: Relevance
“…In another research, it was shown that after load increase in resistance athletes increases the thickness and LVM (26) that this increase is probably due to the nature of resistance training that increases the after load and this after load is the stimulator of the increase in the left ventricular mass and thickness (26). In the researches conducted by Kanakis and Hickson (1980), Fleck et al (1988) and Jerry et al (1999), it is shown that LVM increases after resistance trainings that was consistent with the present research (13,17,19). Maybe the cause of consistency is in the nature of resistance trainings, but in the research conducted by , it was shown that the left ventricular mass decreases after resistance training that is inconsistent with the present research and the cause of the inconsistency is in the age of the subjects (26).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In another research, it was shown that after load increase in resistance athletes increases the thickness and LVM (26) that this increase is probably due to the nature of resistance training that increases the after load and this after load is the stimulator of the increase in the left ventricular mass and thickness (26). In the researches conducted by Kanakis and Hickson (1980), Fleck et al (1988) and Jerry et al (1999), it is shown that LVM increases after resistance trainings that was consistent with the present research (13,17,19). Maybe the cause of consistency is in the nature of resistance trainings, but in the research conducted by , it was shown that the left ventricular mass decreases after resistance training that is inconsistent with the present research and the cause of the inconsistency is in the age of the subjects (26).…”
Section: Discussionsupporting
confidence: 88%
“…When strength training is done, the pressure inside the chest also increases (12). Due to the phenomenon Valsalva maneuver, the drop of the vein blood recession increases significantly and as a result, the heart pulse and the average artery blood pressure increase (13). In those athletes participating in intense isometric, strength or static training (anaerobic, strength and power training), concentric hypertrophy of the left ventricle is created (14).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that HR is the most important factor to determine RPP 27 , and because in all measured moments RPP changes were consistent with HR, tthis fact was confirmed by the present study.…”
Section: Discussionsupporting
confidence: 88%
“…In this context, literature has shown that double-product is a good non-invasive indicator to estimate oxygen demand by the myocardium, at least for continuous aerobic activities 9,10,17 . For non-continuous activities, such as resistance training, RPP measure is not correlated to oxygen demand by the myocardium.…”
Section: Discussionmentioning
confidence: 99%